(untitled) - Nihal Kalıncı; Funda Veren; Tülay Kuzlu Ayyıldız; Hülya Kulakçı Altıntaş (Sağlık Akademisi Kastamonu, 2020)
This study was performed to evaluate psychosocial health status and health practices of pregnant women in Turkey. This comparative descriptive study was conducted at a pregnancy polyclinic of Zonguldak Maternity and Children's Hospital in T between 12.04.2012 – 03.04.2013. A total of 1086 pregnant women participated in the study. Data were collected by using Pregnant Information Form, Pregnancy Psychosocial Health Assessment Scale and Health Practices Questionnaire in Pregnancy-II. Numerical and percentage values, student t test, Mann Whitney-U test, One-Way Analysis of Variance (ANOVA), Kruskal-Wallis variance analysis  and correlation analysis were used for data analysis. In this study, there is a positive correlation between psychosocial health status and health practices of pregnant women (p < .050). However, psychosocial health status and health practices of pregnant women show significant differences based on some characteristics of pregnant women such as age, marital status, family type, education level, employment status, presence of social insurance, economic income, number of children, number of abortion and curettage, chronic disease status, BMI before pregnancy, number of pregnancy, pregnancy planning status, complication associated with pregnancy and social support (p < .050). Besides physical assessments, evaluation of psychosocial health status and health practices of pregnant women, early diagnosis of risky conditions and provision of protective and therapeutic services are recommended during pregnancy follow-ups.